Analysis of carotenoid content and diversity in apricots (Prunus armeniaca L.) grown in China. (15th November 2020) - Zhou, Weiquan; Niu, Yingying; Ding, Xiang; Zhao, Shirong; Li, Yalan; Fan, Guoquan; Zhang, Shikui; Liao, Kang
Highlights: The metabolism of carotenoids in apricot fruit was studied by LC-MS/MS. ε-Carotene, α-cryptoxanthin and apocarotenal were found in apricot fruit. The diversity of carotenoid components and contents of the Central Asian variety group in Xinjiang were explored. β-carotene and (E/Z)-phytoene are the main carotenoids in apricot fruits. The content of carotenoids in the peel of 41 apricot fruits was higher than that in the flesh. Abstract: The carotenoids in the peel and flesh of 41 apricot cultivars were qualitatively and quantitatively analysed by UHPLC-APCI-MS/MS, and the L*, a*, b* and quality indexes of the fruits were determined. The results showed that the L*, a*, b* and quality indexes of the fruits were quite different, and 13 carotenoids were detected in the peel and flesh of apricots, among which ε-carotene, α-cryptoxanthin and apocarotenal were newly detected carotenoids in apricots. The total carotenoid content of the 41 apricot cultivars varied from 20.983 to 320.278 μg/g FW, and the total carotenoid content varied from 17.353 to 222.098 μg/g FW in the peel and from 2.536 to 98.179 μg/g FW in the flesh. The main components of apricot fruits were β-carotene and (E/Z)-phytoene, followed by β-cryptoxanthin and lutein. This study shows that carotenoids in apricot fruits have rich metabolic diversity.